Assessment of surface water resources in Great Ruaha River sub-basin Tanzania: Application of WEAP model for water allocation and utilization impacts analysis - Gervas, Rose; Mulungu, Deogratias M.M.; Nobert, Joel K. (Tanzania Journal of Engineering and Technology, 2019)
The Great Ruaha River (GRR) sub-basin is one of the most important waterways in Tanzania as it supports important economic activities. The sub-basin is progressively faced with an inevitable situation of increasing water demand among competing users while the quantity and quality of water is diminishing. The focus of this study was to assess allocation of existing (2012) and future (up to 2025) quantities of surface water in the GRR sub-basin with consideration of priorities given in the Tanzania Water Resources Management Act, 2009 in the order: domestic, environment, agriculture, livestock and non-domestic. Simulation of water allocation scenarios of irrigation expansion (IE) and implementation of environmental flow requirements (EWD) and their impacts on met demands was done by using WEAP model. Results showed that under current and future conditions, available streamflows are sufficient for the first two water use priorities. Implementation of EWD and IE scenarios will change demands in comparison with reference scenario by 80%, -38% and 45% and shortages by 147%, 123% and 13% in Little Ruaha, Ndembera and Kisigo catchments respectively. To eliminate water shortages, construction of reservoirs, use of alternative supply sources (especially in agriculture) and water demand management measures are recommended. Keywords: Great Ruaha River, Rufiji basin, scenarios, water allocation, water shortage, WEAP model.